PHYSICOCHEMICAL PROPERTIES OF CULMS IN RYE (SECALE CEREALE L.) WITH A BRITTLE STEM - A. A. Konovalov; I. K. Shundrina; E. V. Karpova; V. I. Mamatyuk (Вавиловский журнал генетики и селекции)
Test crosses of rye for the brittle stem character yielded sibs plants with normal and brittle culms. The stems were studied with regard to chemical composition, spectroscopic features and mechanical strength. The normal and fragile culms differed in the content of aromatic lignin monomers and the ratio of various types of chemical bonds.At equal thicknesses, the normal and mutant rye plants differed in the modulus of elasticity and proportional limit. It was found that lateral load breaks stems of mutant plants by the brittle fracture mechanism, and normal plants, by ductile fracture. The normal plants had much higher proportional limits and mechanical strength values.By means of NMR method differences were found in the lignin chemical structure, such as the content of aldehyde and methohyl groups, total aromaticity and the number of ether bonds, by which lignin blocks are linked to carbohydrate fragments of cellular walls.The higher lignin content in the mutant does not improve culm mechanical strength. On the contrary, a decrease in proportional limit and increase in shoot brittleness are observed. Possibly, the bs mutation, in addition to its direct action (culm brittleness) unbalances metabolic processes when forming secondary cellular walls and leads to a deviation from the optimum ratio of carbohydrate and aromatic components. The differences in a number of indicators can be used in breeding programs concerning agricultural traits of stems in cereals.